Material resource management: the role of intensive care unit nurses - Oliveira, Naiara Cristina de; Chaves, Lucieli Dias Pedrereschi (Rev Rene, 2009)
This descriptive and exploratory study aimed to describe the activities related to the management of material resources performed by nurses in the intensive care unit (ICU) of a teaching hospital in the interior of the state of São Paulo, Brazil. Recorded interviews with ICU nurses were used as data collection. They were analyzed according to the content analysis. Recurring aspects were identified in the statements, establishing three thematic cores: Material Purchase, Stock Forecast and Tracking of Material Use. Results evidence the importance of the knowledge of nurses regarding the control of material use, appropriate supervision of team work and that they provide constant training and updating of knowledge, aiming to ensure better financial and quality performance in the use of the material resources needed to provide care to patients.